Difference in Lairage Time Before Slaughtering on Malondialdehyde (MDA) Levels in Landrace Pig Blood Serum - Muhandis, Putri Jauza Aulia; Triakoso, Nusdianto; Saputro, Amung Logam (Universitas Airlangga, 2022)
Lairage time before slaughtering a pig can recover the stress caused by transportation from the farm to the abattoir. Stress conditions can overcome the imbalance between Reactive Oxygen Species (ROS) and the ability of the system to be easily detoxified. Malondialdehyde (MDA) is a specific product of lipid peroxidation, it is often used as a biomarker in research. A total of 18 pigs were divided into two groups, pigs with a lairage time of 6-8 hours and a rest period of 12-24 hours, MDA levels were tested using the Thiobarbituric Acid Reactive Substance (TBARS) method and then analyzed. There was a significant difference (p<0.05) between the group lairage time length of 6-8 hours (18.10 ± 11.616) with a rest period of 12-24 hours (6,80 ± 4,852), there was a decrease in stress levels and was marked by a decreased in levels of MDA in pigs that were rested for 12-24 hours before being slaughtered.